EVALUATION OF THE LEVEL OF STREET LIGHTING ON THE SAFETY ROAD USERS: CASE STUDY OF THE KERTAJATI – KADIPATEN ROAD - Reci Tiana Reta; Amanatullah Savitri (Fakultas Teknik Sipil dan Perencanaan, 2024)
At night, road lighting is very important for a driver. Apart from reducing the number of traffic accidents, good street lighting can also reduce the level of street crime that can occur. As time goes by, human activities are not limited by time. Many people choose to be active day and night to pursue efficiency and effectiveness of time. Apart from playing an important role in various social activities, street lighting is also very important for the sustainability of the traffic system. In this case, the case that occurred on the Kertajati – Kadipaten road was that there was no adequate street lighting. This reduces visibility and also the driver's safety level at night. This research aims to evaluate the location of the Kadipaten – Kertajati road, which does not yet have a good street lighting system, and see the impact on motorists. This research was located on the Kertajati – Kadipaten highway, more precisely on the Babakan Anyar village highway, Kadipaten – Monjot Bridge. The research method used in this research is a qualitative method with perception analysis. The parameters used are the respondents' perception of the importance and satisfaction with street lighting on this road, using a scale of 1 to 5 from not important to very important and not satisfied to very satisfied. Data was processed using the Importance Performance Analysis (IPA) method. Data collected from 40 respondents was divided based on age, gender, and vehicle used when crossing the Kertajati – Kadipaten road. From the results of the questionnaire, the majority of gender who travel the Kertajati – Kadipaten road are women. The age range of the majority who cross the Kadipaten – Kertajati road is ≤ 20 years, while those who rarely cross this road are > 60 years. Meanwhile, the most widely used vehicle is a motorbike.